Case Report: Serum methotrexate monitoring by immunoassay: confusion by by-product, confusion by antidote - Sharma, Aditya; Benoit, Philip; Lansigan, Frederick; Nierenberg, David (Frontiers in Oncology, 2023)
Methotrexate is a commonly used agent in the treatment of many malignancies and rheumatologic/inflammatory diseases. Working by inhibiting dihydrofolate reductase and thereby preventing eventual formation of tetrahydrofolate, methotrexate inhibits synthesis of purines and thymidylate, therefore disabling a malignant cells' ability to replicate. While it is able to effectively do this, methotrexate also holds potential for significant toxicity. Therefore, serum methotrexate monitoring is of utmost importance when administering the drug, particularly when high doses are used. Although there are several different measurement systems, the immunoassay is a commonly used monitoring system that may be prone to interference when using agents with similar carbon backbone as methotrexate, including folinic acid (leucovorin) at high doses, as well as in the setting of glucarpidase use and consequent methotrexate breakdown. However, by adjusting leucovorin dosing policy and being aware of the potential of the immunoassay to be "confused" by similar molecules has allowed for efficient and effective use of the immunoassay while preventing prolonged hospital stays at our institution.